Generalized Joint Hypermobility Associated with Shoulder Pain and Disability in Competitive Swimmers in Denpasar City - Valari, Putu Kavita Krisnina; Puspa Negara, Anak Agung Gede Angga; Kamayoga, I Dewa Gede Alit; Sutirta Yasa, I Wayan Putu (Majalah Ilmiah Fisioterapi Indonesia; Vol 12 No 3 (2024): Majalah Ilmiah Fisioterapi Indonesia, 2024)
Introduction : Generalized joint hypermobility conditions in competitive swimmers can be advantageous as they may enhance athletes' movement speed in the water but can also be a risk factor for shoulder pain. Hypermobility, coupled with repetitive movements, leads to an increased workload on supporting structures, such as muscles, ligaments, and tendons, without sufficient recovery time, thus damaging tissues. The accumulation of loading and tissue damage leads to shoulder pain and disability. This study aims to determine the relationship between Generalized Joint Hypermobility and shoulder pain and disability in competitive swimmers in Denpasar City. Method : This study is an observational analytical study with a cross-sectional approach. The sampling technique used purposive sampling. The sample size obtained from this study was 54 individuals. The joint hypermobility condition was measured using the Beighton score. The Shoulder Pain and Disability Index (SPADI) questionnaire assessed shoulder pain and disability complaints. Results : Based on non-parametric Spearman's rho analysis, the correlation coefficient between Generalized Joint Hypermobility and shoulder pain and disability was obtained at r = 0.686 and r = 0.657, respectively, with a p-value of 0.000 (p < 0.05). Conclusion : This study concludes a significant correlation between generalized joint hypermobility, shoulder pain, and disability in competitive swimmers in Denpasar City.   Keywords: generalized joint hypermobility, shoulder pain, shoulder disability, competitive swimmers